2013
DOI: 10.1007/s10753-013-9796-7
|View full text |Cite
|
Sign up to set email alerts
|

Transcutaneous Electrical Nerve Stimulation (TENS) Accelerates Cutaneous Wound Healing and Inhibits Pro-inflammatory Cytokines

Abstract: The purpose of this study was to evaluate transcutaneous electrical nerve stimulation (TENS) and other common treatment methods used in the process of wound healing in terms of the expression levels of pro-inflammatory cytokines. In the study, 24 female and 24 male adult Wistar-Albino rats were divided into five groups: (1) the non-wounded group having no incision wounds, (2) the control group having incision wounds, (3) the TENS (2 Hz, 15 min) group, (4) the physiological saline (PS) group and (5) the povidon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
50
0
8

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(61 citation statements)
references
References 35 publications
3
50
0
8
Order By: Relevance
“…Gürgen et al reported a significant decrease in the pro‐inflammatory cytokines interleukin‐1 beta (IL‐1β), interleukin‐6 (IL‐6) and tumour necrosis factor‐α (TNF‐α) in the dermis of rat wounds following treatment with transcutaneous electrical nerve stimulation (TENS), a form of ES, compared with other forms of treatment . Their findings suggested that this form of ES shortened the healing process by inhibiting the inflammation phase . On the other hand, studies have reported induced inflammation with ES treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Gürgen et al reported a significant decrease in the pro‐inflammatory cytokines interleukin‐1 beta (IL‐1β), interleukin‐6 (IL‐6) and tumour necrosis factor‐α (TNF‐α) in the dermis of rat wounds following treatment with transcutaneous electrical nerve stimulation (TENS), a form of ES, compared with other forms of treatment . Their findings suggested that this form of ES shortened the healing process by inhibiting the inflammation phase . On the other hand, studies have reported induced inflammation with ES treatment.…”
Section: Discussionmentioning
confidence: 99%
“…To identify the biochemical terms for the search, studies that addressed the subject of inflammatory cytokines will be consulted [20, 22, 3134]. Keywords are selected according to Medical Subject Headings (MeSH) in the National Library of Medicine.…”
Section: Methodsmentioning
confidence: 99%
“…Application of transcutaneous electrical nerve stimulation (TENS) to incisional wounds in rats increased the rate of re‐epithelialization as compared to controls, when 40 mA was applied at a pulse frequency of 2 Hz for 15 min daily for 5 days . There was also a decrease in the expression of the pro‐inflammatory cytokines interleukin‐1 beta, interleukin‐6 and tumour necrosis factor‐alpha in the electrically stimulated group compared to wounded controls.…”
Section: Effects Of Es On Surgical Wounds In Animal Modelsmentioning
confidence: 99%
“…There was also a decrease in the expression of the pro‐inflammatory cytokines interleukin‐1 beta, interleukin‐6 and tumour necrosis factor‐alpha in the electrically stimulated group compared to wounded controls. The authors concluded that electrical stimulation shortened the wound healing process by inhibiting the inflammatory phase. Pulsed current has been shown to have a positive outcome on wound closure; however, this is highly dependent on current intensity, polarity switch and duration of stimulation.…”
Section: Effects Of Es On Surgical Wounds In Animal Modelsmentioning
confidence: 99%